A super wideband circular-shaped fractal antenna loaded with concentric hexagonal slots - Alluri, Srinivasarao; Rangaswamy, Nakkeeran (International Journal of Engineering and Technology, 2018)
This article presents a super wideband (SWB) circular-shaped fourth iterative fractal antenna loaded with concentric hexagonal slots. A tapered microstrip feed and a partial ground plane is used. It has a total size of 40 Ã— 27 Ã— 1.6 mm3. Numerical results of the antenna show that it provides a bandwidth from 1.43 GHz to more than 40 GHz (percentage bandwidth greater than 186%) with a bandwidth ratio of approximately greater than 28:1 for S11 < -10 dB. A prototype of the proposed antenna has been fabricated and its performances are measured up to 15 GHz. A good agreement is achieved between the numerical and experimental reflection coefficient, VSWR and input impedance. Measured radiation patterns at different frequencies and simulated peak gain are presented and discussed. It has the advantages of super wide bandwidth and compact size. The developed antenna is suitable for various wireless communications such as GPS, GSM, UMTS, ISM and UWB.Â Â